2017
DOI: 10.1371/journal.pone.0186668
|View full text |Cite
|
Sign up to set email alerts
|

Melanosis coli: Harmless pigmentation? A case-control retrospective study of 657 cases

Abstract: Backgrounds and aimsThe association of melanosis coli with the development of colorectal polyps remains uncertain.MethodsFrom a total of 18263 patients who had received colonoscopy in our hospital, 219 with melanosis coli cases and 438 controls matched by age and sex (at 1:2 ratio) were included in this study. The association of incidence, number, location, and pathology of colorectal neoplasm with grades and distribution of melanosis coli were analyzed.ResultsMelanosis coli was associated with significantly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 25 publications
5
50
1
5
Order By: Relevance
“…10 In a study that reported the association with non-neoplastic polyps that contain pigment, the toxic effect resulting in the destruction of the apoptotic colonic epithelial cells was claimed to cause the development of the colorectal polyps, as well as melanosis coli. 8 Although no polyp was detected in our case, it was observed that there was no macroscopic and microscopic pigment accumulation in ulcerated tumor tissue in accordance with the literature. Diffuse black-brown pigment was observed on the mucosa and serosal surface of the tumor proximal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…10 In a study that reported the association with non-neoplastic polyps that contain pigment, the toxic effect resulting in the destruction of the apoptotic colonic epithelial cells was claimed to cause the development of the colorectal polyps, as well as melanosis coli. 8 Although no polyp was detected in our case, it was observed that there was no macroscopic and microscopic pigment accumulation in ulcerated tumor tissue in accordance with the literature. Diffuse black-brown pigment was observed on the mucosa and serosal surface of the tumor proximal.…”
Section: Discussionsupporting
confidence: 91%
“…7 It can be seen in varying rates in inflammatory bowel disease, colonic diverticulum, chronic diarrhea, nonsteroidal anti-inflammatory drug use, colorectal polyps and tumors. 5,8 It has been reported in the literature that it is frequently associated with colonic polyps. 5,9 In one study, it was emphasized that pigment-free polyps were more easily detected in endoscopic examination because of the black-brown color of the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although it is frequently located in the colonic mucosa, especially in the the cecum part, MC can be seen in the small intestine as well. 3 However, it may be seen in patients with chronic diarrhea, inflammatory bowel disease, and chronic use of non-steroidal anti-inflammatory drugs. 3,4,5 Improper laxative use due to chronic constipation may cause MC, which is more common in elder patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, it may be seen in patients with chronic diarrhea, inflammatory bowel disease, and chronic use of non-steroidal anti-inflammatory drugs. 3,4,5 Improper laxative use due to chronic constipation may cause MC, which is more common in elder patients. 1,2 Acute appendicitis is one of the most common causes of abdominal pain in patients admitted to the emergency department.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation